2021
DOI: 10.19111/bulletinofmre.941090
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeological and water quality evaluation of parts of River Mamu Sub-Basin, Southeastern Nigeria

Abstract: The water sources in parts of the River Mamu sub-Basin, southeastern Nigeria were evaluated for domestic and agricultural purposes using hydrogeology and water quality. Thirty water samples from both surface water and groundwater were collected and analysed for hydrochemical and biological parameters. The average depth to aquifers and their thicknesses are 109.9 and 11.8m respectively. The concentration of the major ions, TDS and EC are within the WHO permissible guidelines for drinking water. Heavy metals con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…It was observed that topography, lithology, and geology are the major factors that control depth to water table and aquifer thickness in the study area. The present result is agreement with other studies carried out in other locations [8,9,13].…”
Section: Identification Of Aquiferous Units and Regional Water Table ...supporting
confidence: 94%
See 3 more Smart Citations
“…It was observed that topography, lithology, and geology are the major factors that control depth to water table and aquifer thickness in the study area. The present result is agreement with other studies carried out in other locations [8,9,13].…”
Section: Identification Of Aquiferous Units and Regional Water Table ...supporting
confidence: 94%
“…parts of the study area have greater depth to water table. This implies that the water table were observed to mimic the topography of the area[8].…”
mentioning
confidence: 88%
See 2 more Smart Citations